The major cow milk allergen Bos d 5 manipulates T-helper cells depending on its load with siderophore-bound iron. - Franziska Roth-Walter; Luis F Pacios; Cristina Gomez-Casado; Gerlinde Hofstetter; Georg A Roth; Josef Singer; Araceli Diaz-Perales; Erika Jensen-Jarolim (PLoS ONE)
The mechanisms of allergic sensitization to milk are still elusive. The major allergen Bos d 5 belongs to the lipocalin-family and thus is able to transport numerous ligands. In this study we investigated its ability to bind to iron-siderophore complexes and tested the immune-modulatory properties of Bos d 5 in either forms. Structural and in silico docking analysis of Bos d 5 revealed that Bos d 5 is able to bind to iron via catechol-based flavonoids (quercetin, myricetin, luteolin) that act as siderophores as confirmed by spectral-analysis and iron staining. Calculated dissociation constants of docking analyses were below 1 µM by virtual addition of iron. When incubated with human peripheral blood mononuclear cells (PBMCs), only the apo-form of Bos d 5 led to an increase of CD4+positive cells and significantly elevated IL13 and IFNγ-levels. In contrast, holo-Bos d 5 decreased numbers of CD4 expressing cells and induced apoptosis. Taken together, our data give evidence that Bos d 5 is capable of binding iron via siderophores. Moreover, our data support for the first time the notion that the form of application (apo- or holo-form) is decisive for the subsequent immune response. The apo-form promotes Th2 cells and inflammation, whereas the holo-form appears to be immunosuppressive.